International Debt Statistics 2019 - World Bank Group (World Bank, Washington, DC, 2018)
This year’s edition of International Debt Statistics, successor to Global Development Finance and World Debt Tables, is designed to respond to user demand for timely, comprehensive data on trends in external debt in low- and middle-income countries. The World Bank’s Debtor Reporting System (DRS), from which the aggregate and country tables presented in this report are drawn, was established in 1951. World Debt Tables, the first publication that included DRS external debt data, appeared in 1973 and gained increased attention during the debt crisis of the 1980s. Since then, the publication and data have undergone numerous revisions and iterations to address the challenges and demands posed by the global economic conditions. Presentation of and access to data have been refined to improve the user experience. The online edition of International Debt Statistics 2019 now provides a summary overview and a select set of indicators, while an expanded dataset is available online (datatopics.worldbank.org /debt/ids).